Enemies and neighbors Arabs and Jews in Palestine and Israel, 1917-2017 - Black, Ian 1953-2023 (Atlantic Monthly Press, an imprint of Grove Atlantic, 2017)
Enemies and Neighbors is a big, textured, and, crucially, balanced account of over 100 years of the Israel-Palestine conflict, published on the 100th anniversary of the Balfour Declaration (the famous pledge made by the British government on Nov. 2, 1917 expressing sympathy for a national Jewish home in Palestine). 2017 also marks the 50th anniversary of the Six-Day War in June 1967, during which Israel seized its current borders. Much of the existing literature on the Israel-Palestine conflict focuses on the era post-Israeli independence (starting in 1948), has a clear bias, and/or comes at the subject from an academic angle. This is a major, engagingly written trade history covering the entire arc of the conflict up to the present, and Black has done an extraordinary job of telling it from both sides